The Effect of Financial Ratios on Sharia Stock Prices in Companies in the LQ45 Index 2020-2021 - Ikbal Sudarman; Nana Diana (ITB AAS INDONESIA Surakarta, 2022)
This study examines the effect of Debt to Equity Ratio (DER), Net Profit Margin (NPM), Return on Equity (ROE) and Earning Per Share (EPS) on Sharia stock prices included in the LQ45 index. The LQ45 index was chosen because it is a stock that has a high level of liquidity and market capitalization, and it is supported by very good company fundamentals. The method used is a quantitative method. The data used in this study is secondary data taken from the official website of the Indonesian stock exchange. The sample in this study was 30 companies from the 2020-2021 period. The results of the study show that DER, NPM, ROE and EPS simultaneously have a significant effect on Islamic stock prices with F value of 10,765 and R Square of 0.539 or 53.9%. Partially, DER, NPM and ROE have no significant effect on Sharia Stock Prices with a sig. (0.245; 0.291; 0.094). EPS partially has significant effect on Sharia Stock Price with a sig. (0.00).